The Production of Electricity with Photovoltaic Solar Energy in Spain in the 21st Century - Espejo-Marín, Cayetano; Aparicio-Guerrero, Ana Eulalia (Revista de Estudios Andaluces, 2020)
Subsequently, a new Government regulation led to the containment and almost stagnation of the sector until recent dates. At present, a stage of development is taking place as a result of the new commitment to renewable energies to comply with the EU guidelines and the development of self-consumption. The method used has focused on the analysis of the consequences of the decisions of the Governments of Spain in relation to this energy sector, with regard to the evolution of the installed power and its territorial distribution. The results confirm the clear relationship between the policy of incentives and their expansion in the initial stage, the policy of containment and stabilization for a decade and the current situation of new recovery, which is motivated by technological progress and the development of self-consumption, favored in both cases by the enormous reduction in the cost of the facilities.